Applying Skeletal, Histological and Molecular Techniques to Syphilitic Skeletal Remains from the Past - von Hunnius, Tanya (My University, 2004)
Many have been searching for and contemplating the origins of syphilis. By understanding its emergence as a human pathogen we will be better able to elucidate its evolution through time and space as well as shed light on its current state. Ancient DNA techniques used to isolate Treponema pallidum subspecies pallidum DNA from archaeological human specimens provides direct evidence of its existence in the past. To date, only Kolman et al. (1999) have been successful in this endeavour. Along with this protocol, two other published protocols and novel allele specific techniques this thesis aims to add new cases of venereal syphilis identification from historic human remains. To accomplish this, sixteen skeletal samples from different time periods and geographic locations were collected for this project. Of importance are those dating from the Civil War time period from the United States as medical documents state these individuals suffered and/or died from the complications of syphilis. Samples from the United Kingdom are also critical to this analysis as they have confirmed pre-Columbian dates. Along with attempts to isolate bacterial DNA, endogenous DNA (mitochondrial and amelogenin) is analyzed to provide an idea of the different levels of molecular preservation. General preservation as well as the identification of syphilis are also performed using microscopic techniques. By using a tiered approach (macroscopic to microscopic to molecular), a better idea of both preservation and disease presence can be ascertained. Results indicate that although syphilis could be identified at both the macroscopic and microscopic levels for some individuals and endogenous DNA was present, treponemal DNA failed to amplify. Many different reasons are suggested, for example poor conservation methods, misdiagnosis and diagenesis, but the most important possibility is the lack of bacterial DNA in bone at later stages of syphilis which was confirmed using the rabbit model. As a result, the present techniques may not be conducive for treponemal DNA isolation from ancient human remains.
Applying Skeletal, Histological and Molecular Techniques
Keywords: skeletal, histological and molecular techniques; skeletal techniques; histological techniques; molecular techniques; syphilis; syphilitic skeletal remains; skeletal remains; anthropology